Exploring Gender Roles Through Visual Images in Grade 12 English Textbook: A Critical Discourse Analysis Study - Elfani Amanda Rahmadani; Imam Ghozali; Ika Desy Wardani (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
This research explores the representation of gender roles in visual images in grade 12 English textbooks using a critical insight analysis approach. This research uses critical discourse analysis to examine depictions of men and women, aiming to uncover underlying gender biases and stereotypes. By analyzing domestic roles, social roles, depictions of work and activities, use of technology, as well as the frequency and appearance of male and female characters, this research seeks to contribute to the discourse of gender equality in educational materials. The results of the research show that there is a real imbalance in the frequency of appearance of male and female characters, where male characters are depicted more often than female characters in both illustrations and text. In conclusion, although textbooks attempt to present balanced gender roles, certain traditional stereotypes still apply, especially in the frequency of character appearances and the types of roles assigned to each gender. This study highlights the importance of addressing these biases to promote gender equality in educational resources so the authors suggest that educators and textbook developers must be aware of these issues to foster more inclusive learning environments.